Isokinetic Characteristics of Amateur Boxer Athletes - Tasiopoulos, Ioannis; Nikolaidis, Pantelis T.; Tripolitsioti, Alexandra; Stergioulas, Apostolos; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2018)
Aim: The kinetic chain of the punch of boxers is characterized by the contribution of the shoulder; however, the isokinetic muscle strength of shoulder’s rotators muscles has not been well studied so far, especially with regards to performance. Therefore, the aim of the present study was (a) to profile the isokinetic muscle strength of rotators of the glenohumeral joint, bilateral (BL), unilateral (UL) and functional ratios in amateur boxers, and (b) to examine the variation of these muscle strength characteristics by performance level. Methods: Forty male amateur Greek boxers from three division levels (elite, n = 22; second division, n = 11; and third division, n = 7), and 10 non-athletes (control group) were tested, using the isokinetic dynamometer Kin-ComTM in the scapular seated position under standard conditions. We examined (i) peak torque (PT) of internal (IR) and external (ER) rotators during concentric (CON) and eccentric (ECC) contractions at low (60o/s), medium (120o/s) and high speed (180o/s), (ii) BL, (iii) UL, and (iv) functional ratios of dominant (D) and non-dominant (ND) limbs. Results: Boxers were stronger than control group in IR and ER at all speeds, and D outscored ND limb (p<0.05). Elite boxers were stronger than group B and C (p<0.05); however, when peak torque was expressed in relative to body mass values, these differences were attenuated. The BL ratios for the men athletes were under 10% at 60 and 180o/s, the UL ratios were lower at 60 and higher at 180 o/s and significant lower in the dominant limb at all speeds. The functional ratios of IR ECC / ER CON were higher between the control group at all speeds and the ER ECC / IR CON ratios were between 60 and 180o/s, and the two limbs with higher values at 180o/s. Conclusions: Boxers had the strongest dominant limb and their BL ratios were normal at all speeds except of 120o/s ECC. The UL ratios of ECC at 120 and 180o/s of ND were normal, and at the other speeds abnormal due to high IR.